Psychological changes among women with recurrent pregnancy loss during the COVID-19 period in northeastern China: a cross-sectional study - Wang, Tingting; Hou, Yue; Liu, Yilin; Qiao, Chong (Frontiers in Psychology, 2023)
Background It aimed to investigate the prevalence of anxiety and depression in recurrent pregnancy loss (RPL) women and the related factors in Northeastern China during the Coronavirus disease 2019 (COVID-19) pandemic. Methods From March to June 2021, we conducted an electronic questionnaire survey of 267 RPL women who attended the recurrent pregnancy loss clinic at Shengjing Hospital of China Medical University. The State–Trait Anxiety Inventory (STAI), Beck Depression Inventory-II (BDI-II), Perceived Stress Scale (PSS), and Medical Outcomes Study Social Support Survey (MOS-SSS-C) were used to screen for anxiety, depression, stress, and social support. Logistic regression was used to explore the related factors of anxiety and depression. Results RPL women had severe psychological problems during the pandemic: 56.6% showed state anxiety or trait anxiety, 26.6% showed high levels of stress, and 13.1% showed depression. Economic pressure caused by COVID-19, and high stress were common related factors for anxiety and depression. The interval since last miscarriage <6 months, worse mood changes due to COVID-19, and concerns about COVID-19 were associated with anxiety. A history of pregnancy loss >14 weeks was associated with depression. While adequate social support and actively seeking health help were protective factors for trait anxiety. And identifying the etiology was a protective factor for depression. Conclusion The study revealed the prevalence of anxiety, depression, and the associated factors in RPL women during COVID-19. More attention should be paid to the psychology of RPL women and adequate social support should be provided.